Analisis Penggunaan Diksi dalam Berita CNN Indonesia Edisi 2025–2026: Kajian Diksi Gerys Keraf - Andini Aulia Distira; Poppy Adelia Adisty; Ines Amelia; Aulia Uswatun Siagian; Jakaria Jakaria (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This research is motivated by the importance of the appropriate use of diction in online news which influences the clarity and understanding of information by readers. This study aims to analyze the use of diction in CNN Indonesia news edition 2025–2026 based on Gorys Keraf's diction theory study. The research method used is descriptive qualitative with content analysis techniques. The research data was taken from three CNN Indonesia news articles, namely "The Cry of the 'Delayed' CPNS: Absolutely Resigns, Stress Threatened with Unemployment", "Stories from the Village, Graduates Compete for PPSU Vacancies in Jakarta", and "Viral Starlink Levy for Aceh Flood Victims, What are the Facts?" Data in the form of words, phrases, and sentences were analyzed based on the aspects of accuracy, clarity, and appropriateness of diction according to Gorys Keraf. The results of the study show that the use of diction is dominated by denotative diction which is straightforward and informative, but there is still the use of connotative diction, especially in news titles to attract readers' attention, as well as several inaccuracies in word choice that have the potential to cause ambiguity of meaning. The conclusion of this study indicates that the diction in CNN Indonesia news is generally effective, but careful word choice is still needed to ensure clarity and avoid multiple interpretations.